High-performance low-expansion heat-resistant purple sand tea set with far infrared radiation function
By employing an inner and outer double-layer composite structure and co-sintering technology, the problems of insufficient thermal expansion, far-infrared emissivity, and interlayer bonding strength of Zisha teaware during high-temperature use have been solved, resulting in high-performance heat-resistant Zisha teaware with excellent thermal shock resistance and far-infrared radiation function.
Patent Information
- Application Number
- CN202511812436.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-04
- Publication Date
- 2025-12-30
- Estimated Expiration
- 2045-12-04
AI Technical Summary
Existing Zisha teaware suffers from problems such as high thermal expansion coefficient, micro-cracks, low far-infrared emissivity, rapid functional decay, and insufficient interlayer bonding strength when used at high temperatures, making it difficult to meet the safety and functional requirements of high-frequency temperature difference usage scenarios.
It adopts a double-layer composite structure, with an inner layer being a low-expansion reinforcing layer and an outer layer being a far-infrared radiation functional layer, with a quartz sand transition layer in between. Through co-sintering, mechanical interlocking and chemical bonding are formed, with a bonding strength ≥5MPa. The inner layer is composed of purple clay ore, rare earth, hydroxylated cordierite micro powder and mullite particles, while the outer layer is composed of far-infrared radiation powder, purple clay fine powder and high-temperature binder. Combined with rare earth and Fe2O3-ZrO2 coating technology, functional zoning and enhanced bonding are achieved.
It significantly reduces the coefficient of thermal expansion, increases the far-infrared emissivity to 88%, and achieves thermal shock resistance of ≥6 cycles of rapid cooling and heating from 200℃ to 25℃ without damage. It solves the problem of insufficient interlayer bonding strength and meets the requirements of industrial impact resistance testing.
Smart Images

Figure SMS_19
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of ceramic tea sets, and particularly relates to a high-performance low-expansion far-infrared radiation functional heat-resistant purple sand tea set. BACKGROUND
[0002] Purple sand tea sets become important appliances in traditional tea culture due to unique porous structures, good air permeability and heat preservation. With the improvement of the functional requirements of consumers on tea sets, high-performance purple sand tea sets with heat resistance, crack resistance and far-infrared radiation efficiency (promoting the dissolution of tea soup substances) have become a research hotspot. In the prior art, low-expansion minerals and far-infrared functional powders are added to improve the performance, but there are still the following key problems in actual application: The thermal expansion coefficient of the traditional purple sand base body is relatively high, and although the addition of cordierite can reduce the expansion, the interface between the particles and the purple sand base body is weak, which causes microcracks in the sintering process of the base body, and the thermal shock resistance is difficult to meet the high-frequency temperature difference use scene.
[0003] Most of the existing far-infrared powders are added by mechanical mixing, in which silicon carbide is easily oxidized in high-temperature sintering, resulting in a radiation rate of less than 80% in the 8-15 mu band, and the function obviously decays after long-term use; in addition, single material cannot realize the partition design of "base body bearing" and "function strengthening", and the far-infrared radiation and the base body strength are difficult to be considered.
[0004] Some technologies attempt to use a double-layer structure, but the interlayer combination depends on simple physical adhesion, and the problem of layering caused by the difference in thermal expansion of the materials is not solved, and the uneven thickness of the coating is easy to fall off, which cannot pass the test of industrialized mass production.
[0005] The traditional forming process (such as hand kneading and mold pressing) cannot accurately control the density uniformity of the multi-layer structure, and the deformation is caused by the inconsistent shrinkage rate of the inner and outer layers in the sintering process; at the same time, the structure design of the kettle body does not consider the heat dissipation demand, and the surface temperature is too high when used at high temperature, which has a safety hazard. SUMMARY
[0006] The purpose of the present application is to provide a high-performance low-expansion far-infrared radiation functional heat-resistant purple sand tea set to solve the above problems.
[0007] To achieve the above purpose, the present application provides a high-performance low-expansion far-infrared radiation functional heat-resistant purple sand tea set, which adopts an inner-outer double-layer composite structure: The inner layer is a low-expansion reinforced layer, and the raw materials include, by weight percentage, 58-73% of purple sand ore, 2-3% of rare earth, 10-20% of surface hydroxylated cordierite micro powder, 5-15% of mullite particles, and 2-5% of sintering aids; wherein the surface hydroxylated cordierite micro powder has a particle size of 5-10 μm, is obtained by hydroxylating the cordierite micro powder, and is obtained by ultrasonic treatment at 50 ℃ for 2 h using 5% KH-560 silane coupling agent solution; the mullite particles have a particle size of 10-30 μm; and the sintering aids are BaCO3 and ZnO, and the mass ratio of BaCO3 to ZnO is 2:1; The outer layer is a far-infrared radiation functional layer, and the raw materials include, by weight percentage, 30-40% of far-infrared radiation powder, 30-40% of purple sand fine powder, and 10-15% of high-temperature binder; wherein the far-infrared radiation powder includes 25-35% of Fe2O3, 15-25% of ZrO2, and 10-20% of SiC, the SiC is coated with a 5-10 μm thick Fe2O3-ZrO2 composite coating, the purple sand fine powder has a particle size of ≤5 μm, and the high-temperature binder is silica sol with a solid content of 30%; A quartz sand transition layer with a thickness of 0.3-0.5 mm is arranged between the inner layer and the outer layer, the quartz sand with a particle size of 10-20 μm is uniformly distributed at the bonding interface, a mechanical engagement structure is formed by co-sintering, and the bonding strength is ≥5 MPa.
[0008] Preferably, in the above-mentioned high-performance low-expansion far-infrared radiation functional heat-resistant purple sand tea set, the preparation method of the inner layer low-expansion reinforced layer includes: mixing the purple sand ore, the rare earth, the hydroxylated cordierite micro powder, the mullite particles, the sintering aids, and deionized water in a mass ratio of 1:0.35-0.4, and then performing vacuum pugging to obtain the inner layer mud after aging for 20 days in an environment with a humidity of 90% and a temperature of 25 ℃; wherein the vacuum degree of the vacuum pugging is -0.09 MPa, and the pugging time is 20 min.
[0009] Preferably, in the above-mentioned high-performance low-expansion far-infrared radiation functional heat-resistant purple sand tea set, the far-infrared radiation powder, the purple sand fine powder, and the silica sol are mixed to form functional particles with a particle size of 0.1-0.3 mm by a spray granulation method, and then deionized water is added to prepare the outer layer mud with a water content of 22-25%.
[0010] Preferably, in the above-mentioned high-performance low-expansion far-infrared radiation functional heat-resistant purple sand tea set, the quartz sand of the quartz sand transition layer is pre-sintered at 1000 ℃ for 2 h, has a surface roughness Ra of 1.6-3.2 μm, is uniformly scattered on the surface of the inner layer body, and is covered with the outer layer mud for composite forming, and the amount of the quartz sand is 5-10 g. m 2 .
[0011] Preferably, in the above-mentioned high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set, the forming method of the composite structure is: using a segmented forming process, first forming the inner layer clay into a shape by a mold with a pressure of 5-10 MPa, then drying to a moisture content of 10-12%, laying a quartz sand transition layer on the surface, and then coating the outer layer of functional layer clay to form a whole body by secondary forming with a pressure of 3-5 MPa.
[0012] Preferably, in the above-mentioned high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set, the thermal expansion coefficient of the inner layer low-expansion reinforcing layer is ≤3.0×10 -6 Preferably, in the above-mentioned high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set, the thermal expansion coefficient of the inner layer low-expansion reinforcing layer is ≤3.0×10
[0013] Preferably, in the above-mentioned high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set, the sintering process is a segmented sintering process: Low-temperature section, sintering conditions: room temperature-400℃, heating rate 5℃ min, holding for 1h, removing organic matter; Medium-temperature section, sintering conditions: 400-1000℃, heating rate 3℃ min, holding for 2h, passing 5% volume concentration N2 protective gas to realize crystal type conversion; High-temperature section, sintering conditions: 1000-1220℃, heating rate 2℃ min, holding for 3h, oxygen content ≤1%, completing co-sintering to form chemical-mechanical dual combination of the inner and outer layers through the quartz sand transition layer.
[0014] Preferably, in the above-mentioned high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set, the inner layer wall thickness of the kettle body is 2-3mm, the outer layer wall thickness is 0.5-1mm, and the overall wall thickness is 3-4mm; the kettle spout and the inner layer base are connected in an embedded manner, the connection depth is 5-8mm, and the outer layer functional layer covers the connection interface to form a sealed transition zone.
[0015] Preferably, in the above-mentioned high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set, the far-infrared radiation functional layer and the inner layer form an interlocking combination structure, and the quartz sand particles are embedded in the inner and outer layer bases with a depth of ≥50μm.
[0016] A preparation method of a high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set as described above, comprising the following steps: (1) Preparation of inner layer clay: crush the purple clay ore to 200 mesh, mix it with rare earth, hydroxylated cordierite powder, mullite particles and sintering aid, make slurry at a water-to-material ratio of 0.35:1, and vacuum knead the clay for 20 minutes. (2) Preparation of outer functional particles: far-infrared powder, purple clay fine powder and silica sol are spray granulated to obtain functional particles; (3) Composite molding: After the inner blank is formed, a quartz sand transition layer is laid, and the outer functional layer clay is wrapped around it for secondary molding; (4) Segmented sintering: sintering is completed according to the low temperature debinding, medium temperature protection and high temperature co-sintering system to obtain the finished product.
[0017] Therefore, the present invention employs the above-mentioned high-performance, low-expansion, and far-infrared radiation-functional heat-resistant purple clay teaware, which has the following beneficial effects: (1) Rare earth elements can reduce the coefficient of thermal expansion, increase density, and enhance structural stability. During sintering, rare earth elements can form a eutectic liquid phase with sintering aids, filling grain boundary pores and accelerating ion diffusion. Adding rare earth elements can cause lattice distortion, increase grain boundary stress, and offset thermal expansion at high temperatures. Hydroxylated cordierite forms -OH groups on the particle surface through silane coupling agent (KH-560), forming hydrogen bonds with Al-OH and Si-OH in purple clay. After sintering, it is converted into Si-O-Al covalent bonds, achieving chemical bonding and strengthening. The Fe2O3-ZrO2 coating layer forms a dense oxide barrier layer (melting point ≥1500℃) during sintering. Combined with a nitrogen protective atmosphere, it inhibits the oxidation reaction of SiC in the 1000-1220℃ range, retaining the core radiative components. Through the elastic buffering effect of the quartz sand transition layer, the interfacial thermal stress during sintering is reduced, avoiding crack initiation.
[0018] (2) Through the modification technology of inner layer hydroxylated cordierite micro powder, the interfacial bonding strength between cordierite and purple clay matrix is improved. Combined with the skeleton support of mullite particles, the inner thermal expansion coefficient is reduced, and the thermal shock resistance reaches ≥6 cycles of rapid cooling and heating from 200℃ to 25℃ without damage, which is an improvement over traditional teaware and solves the problem of temperature difference cracking.
[0019] (3) The outer layer adopts the SiC surface coating Fe2O3-ZrO2 composite coating technology (coating thickness 5-10μm). The dual-layer structure realizes functional partitioning. The inner layer provides a high-strength, low-expansion substrate, while the outer layer focuses on far-infrared radiation, avoiding performance compromise of a single material.
[0020] (4) The quartz sand transition layer technology forms a dual combination of "mechanical interlocking and chemical bonding" during the co-sintering process. Scanning electron microscopy shows that the quartz sand particles are embedded in the inner and outer layers to a depth of ≥50μm, forming an interlocking interface structure, which completely solves the problem of delamination and meets the requirements of industrial impact resistance testing.
[0021] The technical solution of the present invention will be further described in detail below through embodiments. Detailed Implementation
[0022] To better understand the above technical solutions, a detailed description of the specific implementation methods will be provided below. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0023] The terminology used in the embodiments of this invention is for the purpose of describing particular embodiments only and is not intended to limit the invention. The singular forms “a,” “the,” and “the” as used in the embodiments of this invention and the appended claims are also intended to include the plural forms, and “multiple” generally includes at least two unless the context clearly indicates otherwise.
[0024] It should also be noted that the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that an article or device that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such an article or device. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the article or device that includes said element.
[0025] This invention provides a high-performance, low-expansion, far-infrared radiation-functional heat-resistant purple clay teaware, wherein the teaware adopts an inner and outer double-layer composite structure: The inner layer is a low-expansion reinforcing layer. The raw materials, by weight percentage, include: 58-73% purple clay ore, 2-3% rare earth elements, 10-20% surface-hydroxylated cordierite powder, 5-15% mullite particles, and 2-5% sintering aid. Among them, the surface-hydroxylated cordierite powder has a particle size of 5-10 μm and is obtained by hydroxylating cordierite powder and then ultrasonically treating it at 50℃ for 2 hours with a 5% KH-560 silane coupling agent solution. The mullite particles have a particle size of 10-30 μm. The sintering aid consists of BaCO3 and ZnO, with a BaCO3 to ZnO mass ratio of 2:1. The outer layer is a far-infrared radiation functional layer. The raw materials, by weight percentage, include: 30-40% far-infrared radiation powder, 30-40% purple clay fine powder, and 10-15% high-temperature binder. Among them, the far-infrared radiation powder includes 25-35% Fe2O3, 15-25% ZrO2, and 10-20% SiC. The SiC surface is coated with a 5-10μm thick Fe2O3-ZrO2 composite coating. The purple clay fine powder has a particle size of ≤5μm. The high-temperature binder is silica sol with a solid content of 30%. A quartz sand transition layer with a thickness of 0.3-0.5 mm is set between the inner and outer layers. It is composed of quartz sand with a particle size of 10-20 μm, which is uniformly distributed at the bonding interface and formed by co-sintering to form a mechanical interlocking structure with a bonding strength ≥5 MPa.
[0026] To further optimize the above technical solution, the preparation method of the inner low-expansion reinforcing layer includes: mixing purple clay ore, rare earth, hydroxylated cordierite powder, mullite particles, sintering aid and deionized water at a mass ratio of 1:0.35-0.4, and after vacuum kneading, aging in an environment with 90% humidity and 25℃ for 20 days to obtain the inner layer clay material; wherein, the vacuum degree of vacuum kneading is -0.09MPa and the kneading time is 20min.
[0027] To further optimize the above technical solution, far-infrared radiation powder, purple clay fine powder and silica sol are mixed and made into functional particles with a particle size of 0.1-0.3mm by spray granulation. Deionized water is added to prepare an outer layer of clay with a moisture content of 22-25%.
[0028] To further optimize the above technical solution, the quartz sand in the transition layer is pre-fired at 1000℃ for 2 hours, with a surface roughness Ra of 1.6-3.2μm. It is then evenly spread on the surface of the inner layer blank, and then covered with the outer layer of clay for composite molding. The dosage is 5-10g. m 2 .
[0029] To further optimize the above technical solution, the molding method of the composite structure is as follows: adopt a segmented molding process, first press the inner layer of clay material into shape through a mold at a pressure of 5-10 MPa, then dry it to a moisture content of 10-12%, lay a quartz sand transition layer on the surface, and then cover it with the outer functional layer of clay material. The whole blank is formed by secondary molding at a pressure of 3-5 MPa.
[0030] To further optimize the above technical solution, the coefficient of thermal expansion of the inner low-expansion reinforcement layer is ≤3.0×10⁻⁶. -6 / ℃, water absorption rate ≤1.0%, providing a high-temperature impact resistant substrate for the outer functional layer; the outer far-infrared radiation functional layer has an emissivity ≥88% in the 8-15μm band and a thickness of 0.5-1mm.
[0031] To further optimize the above technical solution, the sintering process is segmented sintering: In the low-temperature section, the sintering conditions are room temperature - 400℃, with a heating rate of 5℃. min, keep warm for 1 hour, remove organic matter; In the medium-temperature range, the sintering conditions are 400-1000℃, with a heating rate of 3℃. min, keep warm for 2h, and introduce 5% volume concentration N2 protective gas to achieve crystal transformation; In the high-temperature section, the sintering conditions are 1000-1220℃, with a heating rate of 2℃. The process involves holding the material at room temperature for 3 hours with an oxygen content ≤1% to complete co-sintering, thereby achieving a chemical-mechanical dual bond between the inner and outer layers through a quartz sand transition layer.
[0032] To further optimize the above technical solution, the inner wall thickness of the kettle body is 2-3mm, the outer wall thickness is 0.5-1mm, and the overall wall thickness is 3-4mm; the spout and the inner substrate are connected by an embedded connection with a connection depth of 5-8mm, and the outer functional layer covers the connection interface to form a sealed transition area.
[0033] To further optimize the above technical solution, the far-infrared radiation functional layer and the inner layer form an interlocking structure, and the quartz sand particles are embedded in the inner and outer matrix to a depth of ≥50μm.
[0034] A method for preparing a high-performance, low-expansion, far-infrared radiation-functional heat-resistant purple clay teapot as described above includes the following steps: (1) Preparation of inner layer clay: crush the purple clay ore to 200 mesh, mix it with rare earth, hydroxylated cordierite powder, mullite particles and sintering aid, make slurry at a water-to-material ratio of 0.35:1, and vacuum knead the clay for 20 minutes. (2) Preparation of outer functional particles: far-infrared powder, purple clay fine powder and silica sol are spray granulated to obtain functional particles; (3) Composite molding: After the inner blank is formed, a quartz sand transition layer is laid, and the outer functional layer clay is wrapped around it for secondary molding; (4) Segmented sintering: sintering is completed according to the low temperature debinding, medium temperature protection and high temperature co-sintering system to obtain the finished product.
[0035] To provide a clearer and more detailed description of the high-performance, low-expansion, far-infrared radiation-functional heat-resistant purple clay teaware provided by the embodiments of the present invention, the following description will be based on specific embodiments.
[0036] Example 1 Inner low-expansion reinforcing layer: 68% purple clay ore, 2% rare earth elements, 15% hydroxylated cordierite powder, 10% mullite particles, and 5% sintering aid; among which, the purple clay ore is purple mud, with 60% SiO2 and 22% Al2O3; the hydroxylated cordierite powder has a particle size of 5-10μm, is treated with KH-560 for 2h, and has a hydroxylation degree of 85%; the mullite particles have a particle size of 20μm, and the sintering aid is BaCO3 and ZnO, with BaCO3:ZnO=2:1; Outer far-infrared radiation functional layer: 35% far-infrared powder, 40% purple clay fine powder, and 25% silica sol; among which, the far-infrared powder includes 30% Fe2O3, 20% ZrO2, and 15% SiC, with an 8μm SiC coating layer; the purple clay fine powder has a particle size ≤5μm; and the silica sol has a solid content of 30%. Quartz sand transition layer: particle size 15μm, pre-fired at 1000℃ for 2h, surface roughness Ra2.0μm; Preparation steps: Inner layer mud preparation: the raw materials and deionized water are mixed at a ratio of 1:0.35, and the mixture is treated in a vacuum pumice machine at -0.09MPa for 20 minutes at a temperature of 25℃ and a humidity of 90%. It is then aged for 20 days, with mechanical turning every 3 days during this period.
[0037] For the preparation of outer functional particles, far-infrared powder is mixed with purple clay fine powder and silica sol and then sprayed into granules. The inlet air temperature is 180℃ and the outlet air temperature is 90℃ to obtain 0.2mm particles. Water is added to adjust the moisture content to 23%.
[0038] Composite molding: the inner layer of clay is pressed into shape using a mold at a pressure of 8 MPa, dried to a moisture content of 12%, and then 8 g of quartz sand is evenly sprinkled on the surface. m 2 The outer layer of clay is coated and formed twice under a pressure of 4MPa, resulting in a teapot body with an inner wall thickness of 2.5mm and an outer wall thickness of 0.8mm.
[0039] Segmented sintering, low-temperature section: room temperature - 400℃, heating rate of 5℃. min, keep warm for 1 hour; Medium temperature range: 400-1000℃, heating rate is 3℃. min, introduce 5% N2, keep warm for 2 hours; High temperature range: 1000-1200℃, heating rate is 2℃. min, oxygen content ≤1%, hold for 3 hours, then cool with the furnace.
[0040] Performance testing: Coefficient of thermal expansion: 2.8 × 10⁻⁶ -6 ℃; Far-infrared emissivity (8-15μm): 89%; Thermal shock resistance: No damage after 7 cycles of 200℃-25℃; Interlayer bond strength: 5.5 MPa (tensile test); Surface temperature (water temperature at 100℃): 52℃.
[0041] Example 2 The only difference from Example 1 is that the temperature of the high-temperature sintering section is 1220°C, while the other parameters are the same.
[0042] Performance differences: Far-infrared emissivity increased to 90%, SiC oxidation rate further decreased, and coefficient of thermal expansion slightly increased to 3.0×10⁻⁶. -6 At ℃, it showed no damage after 6 thermal shock tests, but the increased sintering shrinkage led to micro-stress.
[0043] Example 3 The inner layer formula was adjusted to: 62% purple clay ore, 3% rare earth, 20% hydroxylated cordierite, 8% mullite, and 7% sintering aid. The remaining parameters were the same as in Example 1.
[0044] Performance differences: The coefficient of thermal expansion is reduced to 2.5×10. -6 The temperature was ℃, but the thermal shock resistance dropped to 6 times. The excessive cordierite content led to a decrease in the toughness of the matrix, and the bonding strength was 5.2 MPa.
[0045] Comparative Example 1 Raw material formula: 75% purple clay ore, 15% unmodified cordierite, 5% mullite, 5% firing aid (single material, without outer layer and transition layer).
[0046] Preparation process: Traditional mold forming, air sintering, 1200℃, 3h.
[0047] Performance comparison: Coefficient of thermal expansion 4.5×10 -6 ℃, thermal shock resistance after 4 failures, no far-infrared radiation function, no interlayer bonding problems.
[0048] Comparative Example 2 Structural design: inner layer The outer layer material is the same as in Example 1, but it is directly bonded together (without a quartz sand transition layer).
[0049] Performance comparison: interlayer bonding strength 3.2MPa, delamination during tensile test, outer layer detached after 5 thermal shock cycles, surface temperature 60℃, heat dissipation structure is the same, but abnormal heat conduction is caused by delamination.
[0050] Comparative Example 3 Structural design: Single-layer purple clay substrate, formula is the same as comparative example 1, outer layer is sprayed with a coating of far-infrared powder and binder, thickness 2mm.
[0051] Preparation process: After the substrate is sintered, a second coating is sprayed on, followed by low-temperature sintering at 1000℃.
[0052] Performance comparison: Far-infrared emissivity 82%, SiC oxidation rate 25%, coating bonding strength 2.5MPa, easy to peel off, coating cracks after 3 thermal shocks.
[0053] The data comparison between Examples 1-3 and Comparative Examples 1-3 is shown in Table 1 below; Table 1 Comparison of Data Between Examples and Comparative Examples
[0054] Necessity of hydroxylation modification: In Comparative Example 1, unmodified cordierite resulted in an increase in the coefficient of thermal expansion of 1.7 × 10⁻⁶.-6 At ℃, the thermal shock resistance decreased by 42%, demonstrating the key role of surface modification in interfacial bonding and thermal stability.
[0055] The role of the quartz sand transition layer: In Comparative Example 2, the bonding strength decreased by 42% without the transition layer, and the thermal shock resistance decreased by 29% due to delamination failure, verifying the irreplaceable role of the transition layer in suppressing interfacial stress.
[0056] Advantages of the dual-layer structure: The emissivity and bonding strength of the single coating in Comparative Example 3 are significantly lower than those in the Example, demonstrating the breakthrough of the co-sintered dual-layer structure in terms of functional stability and structural reliability.
[0057] By comparing the examples and comparative examples, the synergistic effect of raw material surface modification, quartz sand transition layer bonding, and double-layer co-sintering process in this invention is fully verified. Moreover, the preparation process can be realized by conventional ceramic equipment, which makes it feasible for industrial production.
[0058] Therefore, the high-performance, low-expansion, far-infrared radiation-functional heat-resistant purple clay teaware of the present invention utilizes rare earth elements in its raw materials. This reduces the coefficient of thermal expansion, increases density, and enhances structural stability. During sintering, rare earth elements can form a eutectic liquid phase with the sintering aid, filling grain boundary pores and accelerating ion diffusion. The addition of rare earth elements can also cause lattice distortion, increasing grain boundary stress and offsetting thermal expansion at high temperatures. Hydroxylated cordierite forms -OH groups on the particle surface through a silane coupling agent (KH-560), forming hydrogen bonds with Al-OH and Si-OH in the purple clay. After sintering, these groups transform into Si-O-Al covalent bonds, achieving chemical bonding and strengthening. The Fe2O3-ZrO2 coating layer forms a dense oxide barrier layer (melting point ≥1500℃) during sintering. Combined with a nitrogen protective atmosphere, this inhibits the oxidation reaction of SiC in the 1000-1220℃ range, preserving the core radiating components. The elastic buffering effect of the quartz sand transition layer reduces interfacial thermal stress during sintering, preventing crack initiation.
[0059] Through the modification technology of inner layer hydroxylated cordierite micro powder, the interfacial bonding strength between cordierite and purple clay matrix is improved. Combined with the skeletal support of mullite particles, the coefficient of thermal expansion of the inner layer is reduced, and the thermal shock resistance reaches ≥6 cycles of rapid cooling and heating from 200℃ to 25℃ without damage. This is an improvement over traditional teaware and solves the problem of temperature difference cracking.
[0060] The outer layer employs a SiC surface coated with a Fe2O3-ZrO2 composite coating technology (coating thickness 5-10μm). This dual-layer structure achieves functional zoning, with the inner layer providing a high-strength, low-expansion substrate and the outer layer focusing on far-infrared radiation, avoiding performance compromises associated with single materials. The quartz sand transition layer technology forms a dual bond of "mechanical interlocking and chemical bonding" during co-sintering. Scanning electron microscopy reveals that quartz sand particles are embedded in the inner and outer layers to a depth ≥50μm, forming an interlocking interface structure that completely solves the delamination problem and meets the requirements of industrial impact resistance testing.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A high-performance low-expansion heat-resistant purple sand tea set with far infrared radiation function, characterized in that, The tea set adopts a double-layer composite structure: The inner layer is a low-expansion reinforced layer, and the raw materials include, by weight percentage, 58-73% of purple sand ore, 2-3% of rare earth, 10-20% of surface-hydroxylated cordierite micro powder, 5-15% of mullite particles, and 2-5% of sintering aids; the surface-hydroxylated cordierite micro powder has a particle size of 5-10 μm, is obtained by hydroxylating the cordierite micro powder, and is obtained by ultrasonic treatment at 50°C for 2 h using 5% KH-560 silane coupling agent solution; the mullite particles have a particle size of 10-30 μm; and the sintering aids are BaCO3 and ZnO, and the mass ratio of BaCO3 to ZnO is 2:1; The outer layer is a far-infrared radiation functional layer, and the raw materials include, by weight percentage, 30-40% of far-infrared radiation powder, 30-40% of purple sand fine powder, and 10-15% of high-temperature binder; the far-infrared radiation powder includes 25-35% of Fe2O3, 15-25% of ZrO2, and 10-20% of SiC, the SiC is coated with a 5-10 μm-thick Fe2O3-ZrO2 composite coating, the purple sand fine powder has a particle size of ≤5 μm, and the high-temperature binder is silica sol with a solid content of 30%; A quartz sand transition layer is arranged between the inner and outer layers, has a thickness of 0.3-0.5 mm, and is formed by uniformly distributing quartz sand particles with a particle size of 10-20 μm at the bonding interface, and is formed into a mechanical engagement structure by co-sintering, and has a bonding strength of ≥5 MPa.
2. The high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set according to claim 1, characterized in that, The preparation method of the inner layer low-expansion reinforced layer includes: mixing the purple sand ore, the rare earth, the hydroxylated cordierite micro powder, the mullite particles, the sintering aids, and deionized water at a mass ratio of 1:0.35-0.4, performing vacuum pugging, and then aging for 20 days in an environment with a humidity of 90% and a temperature of 25°C to obtain the inner layer mud; 3. The high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set according to claim 1, characterized in that, The far-infrared radiation powder, the purple sand fine powder, and the silica sol are mixed to form functional particles with a particle size of 0.1-0.3 mm by a spray granulation method, and deionized water is added to prepare the outer layer mud with a water content of 22-25%.
4. The high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set according to claim 1, characterized in that, The quartz sand of the quartz sand transition layer is pre-fired at 1000 DEG C for 2 hours, has a surface roughness of 1.6-3.2 microns, is uniformly scattered on the surface of the inner layer blank, and is then covered with the outer layer clay for composite molding, and the amount is 5-10 g m 2 .
5. The high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set according to claim 1, characterized in that, The forming method of the composite structure includes: first, the inner layer mud is formed by pressing through a mold at a pressure of 5-10 MPa, then dried to a water content of 10-12%, and then the quartz sand transition layer is laid on the surface, and then the outer layer functional layer mud is coated to form an integrated body by secondary forming at a pressure of 3-5 MPa.
6. The high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set according to claim 1, characterized in that, The thermal expansion coefficient of the inner layer low-expansion reinforcing layer is ≤3.0×10 -6 The outer layer far infrared radiation functional layer has a radiation rate ≥88% in the 8-15 μm wave band and a thickness of 0.5-1 mm.
7. The high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set according to claim 1, characterized in that, The sintering process is a segmented sintering process: Low temperature stage, sintering condition is room temperature-400℃, heating rate 5℃ min, holding 1 h, excluding organic matter; The sintering conditions in the medium temperature section are 400-1000°C, and the heating rate is 3°C / min min, and the temperature was kept for 2h. The crystal form was converted by introducing 5% volume concentration N2protective gas. High temperature section, sintering conditions for 1000-1220 ℃, heating rate 2 ℃ min, holding 3h, oxygen content ≤1%, complete co-sintering, make the inner and outer layers through the quartz sand transition layer to form chemical-mechanical double combination.
8. The high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set according to claim 1, characterized in that, The inner layer of the tea set has a wall thickness of 2-3 mm, the outer layer has a wall thickness of 0.5-1 mm, and the overall wall thickness is 3-4 mm; the spout and the inner layer base are connected in an embedded manner, the connection depth is 5-8 mm, and the outer layer functional layer covers the connection interface to form a sealed transition zone.
9. The high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set according to claim 1, characterized in that, The far-infrared radiation functional layer and the inner layer form an interlocking bonding structure, and the quartz sand particles are embedded in the inner and outer layer bases to a depth of ≥50 μm.
10. A method for preparing a high-performance low-expansion and far-infrared radiation functional heat-resistant purple sand tea set according to any one of claims 1-9, characterized in that, The method includes the following steps: (1) Inner layer mud preparation: the purple sand ore is crushed to 200 mesh, mixed with the rare earth, the hydroxylated cordierite micro powder, the mullite particles, and the sintering aids, and prepared into a slurry at a water-to-material ratio of 0.35:1, and vacuum pugged for 20 min; (2) The outer functional particle preparation, the far infrared powder, the purple sand fine powder and the silica sol are sprayed to prepare the functional particle; (3) The composite molding, after the inner layer blank body is formed, the quartz sand transition layer is laid, the outer layer functional layer mud is coated, and the secondary molding is carried out; (4) The sectional sintering is completed according to the low-temperature glue removal, the medium-temperature protection and the high-temperature co-sintering system, and the finished product is prepared.
Citation Information
Patent Citations
Ceramic ware inner coating material with far-infrared strengthening function, preparation method therefor and application of ceramic ware inner coating material
CN106518167A
Purple sand tea set with inner layer made of rare earth material and method thereof
CN118619650A
Ceramic material as well as preparation method and application thereof
CN120441287A
Multi-functional health pot
CN2113686U
Far infrared energy-saving radiation coating for high-temperature furnace
JP2021095326A